An indicator of well-being for Italian agriculture - Mafalda Monda; Giuliano Gabrieli; Matteo Mazziotta (Italian Review of Agricultural Economics (REA), 2021)
The paper presents a composite indicator of well-being for Italian agriculture.Well-being is defined as the health condition of the agricultural sector from the point of view of farmers. The indicator is based on four dimensions: social, environmental, institutional and economic, allowing comparability of well-being at regional level. The novelty of the approach consists in presenting a well-being indicator at sectorial level, by applying a new method of aggregation, the Adjusted Mazziotta-Pareto index (2016). It is a non-compensatory approach for summarizing a set of individual indicators which accounts for unbalanced distribution among the indicators. Results show that central and northern regions are in the top ten for the regional agricultural well-being in years 2013 and 2016.
Keywords: Q01; R11; Q18; 330; agriculture; composite index; farmers; sustainability; well-being